Effects of neoadjuvant zoledronate and radiation therapy on cell survival, cell cycle distribution, and clinical status in canine osteosarcoma - Norquest, Carissa J.; Rogic, Anita; Gimotty, Phyllis A.; Maitz, Charles A.; Rindt, Hansjorg; Ashworth, Hayley L.; Bryan, Jeffrey N.; Donnelly, Lindsay L.; McCleary-Wheeler, Angela L.; Flesner, Brian K. (Frontiers in Veterinary Science, 2024)
Zoledronic acid (ZOL) is a third-generation bisphosphonate with higher affinity for bone resorption areas than earlier bisphosphonates (i.e. pamidronate, PAM). In human medicine, ZOL provides improved bone pain relief and prolonged time to skeletal-related events compared to its older generational counterparts. Preclinical studies have investigated its role as an anti-neoplastic agent, both independently and synergistically, with radiation therapy (RT). ZOL and RT act synergistically in several neoplastic human cell lines: prostate, breast, osteosarcoma, and fibrosarcoma. However, the exact mechanism of ZOL's radiosensitization has not been fully elucidated. We investigated ZOL's ability to induce apoptosis in canine osteosarcoma cell lines treated with various doses of megavoltage external beam radiotherapy. Secondly, we evaluated cell cycle arrest in ZOL-treated cells to assess several neo-adjuvant timepoints. Finally, we treated 20 dogs with naturally occurring appendicular OS with 0.1 mg/kg ZOL IV 24 hours prior to receiving 8 Gy of RT (once weekly fraction x 4 weeks). We found that apoptosis was increased in all ZOL-treated cell lines compared to controls, and the combination of ZOL and RT resulted in dissimilar apoptosis between Abrams and D-17, and HMPOS cell lines. Cell cycle arrest (G2/M phase) was minimal and variable between cell lines, but perhaps greatest at 48 hours post ZOL treatment. Only 10% of dogs treated with ZOL and RT developed pathologic fracture, compared to 44% of dogs historically treated with PAM and RT (p=0.027). ZOL and RT appear to be a well-tolerated combination treatment scheme for non-surgical candidates; future studies must elucidate the ideal timing of ZOL.